Durchl {\ "a} ssigkeitsorientierte Bildung - Keil, Reinhard; Niehus, Dominik; Ossenschmidt, Daniel

Automatic emotion recognition - technologies, interpretation and applications - Brand, Marcel; Klompmaker, Florian; Schleining, Peter; Weiss, Fabian (Computer science spectrum)

Enriching Disaster Control Management based on Human-Centered Design - Fischer, Holger Gerhard; Klompmaker, Florian (Proceedings of the 9th International Conference on Information Systems for Crisis Response and Management (ISCRAM), Vancouver, Kanada)

German UPA Qualitätsstandard für Usability Engineering - Behrenbruch, Kay; Bogner, Christian; Fischer, Holger Gerhard; Geis, Thomas; Geitner, Claudia; Heimgärtner, Rüdiger; Hofmann, Britta; Hunkirchen, Peter; Kluge, Oliver; Litzenberg, Britta; Molich, Rolf; Polkehn, Knut; et al.

Learning scenarios for school 2.0 - Jakoblew, Marcel; Niehus, Dominik; Selke, Harald
In order to support everyday school life, the educational platform "Education in Dialogue" was developed and continuously improved over a period of more than ten years in an evolutionary process with user participation. The aim of this article is to show how sustainable support can be achieved by not focusing on the basic possibilities of network-based work, but using everyday practice as a starting point. In order to decide how the school assignment can be optimally supported in a specific embodiment, we develop »learning scenarios«. Based on a didactic approach, a technical concept and a usage guide are designed.

E-learning strategies: best practice or careful structural renewal? - Keil, Reinhard; Schild, Christian; Winkelnkemper, Felix

dSensingNI – A Framework for Advanced Tangible Interaction using a Depth Camera - Klompmaker, Florian; Nebe, Karsten; Fast, Alex
This work presents an approach to overcome the disadvantages of existing interaction frameworks and technologies for touch detection and object interaction. The robust and easy to use framework dSensingNI (Depth Sensing Natural Interaction) is described, which supports multitouch and tangible interaction with arbitrary objects. It uses images from a depth-sensing camera and provides tracking of users fingers of palm of hands and combines this with object interaction, such as grasping, grouping and stacking, which can be used for advanced interaction techniques.

Authenticated Tangible Interaction using RFID and Depth-Sensing Cameras - Supporting Collaboration on Interactive Tabletops - Klompmaker, Florian; Fischer, Holger Gerhard; Jung, Helge (Proceedings of the 5th International Conference on Advances in Computer-Human Interaction (ACHI), Valencia, Spanien)

Designing Multi-Modal Map-Based Interfaces for Disaster Management - Paelke, Volker; Nebe, Karsten; Geiger, Christian; Klompmaker, Florian; Fischer, Holger Gerhard (Proceedings of the 5th International Conference on Advances in Computer-Human Interaction (ACHI), Valencia, Spanien)

Computer science and society - a lecture in the master's degree in computer science - Selke, Harald (FIfF communication)
There have been and still are lectures on the subject of computer science and society at some universities. Some of these are still held by those who can be considered the founders of this subject in Germany. In recent years, however, some of the protagonists from the very beginning have already retired and the positions have been filled or partially rededicated with successors of various origins. Aspects that were previously dealt with within this subject are now addressed in other subjects. For the "new" lecturers the question arises how the problem that Stefan Köpsell formulated very honestly can be addressed: "Since I have not yet known any satisfactory systematics for computer science and society, the lecture consists of a collection of widely spread, each separately understandable themed mosaic tiles. Everyone has to put their overall understanding of the topic together personally. ”(Köpsell, 2012) In this contribution, attempts to design a lecture Computer Science and Society within the given framework (previous lectures, content-related delimitation of other events, supplementary events, previous knowledge and Expectations of the students) and the experiences associated with the implementation are reported. As presumably every course, this represents work in progress. delimitation of the content of other events, supplementary events, previous knowledge and expectations of the students) and the experiences associated with the implementation are reported. As presumably every course, this represents work in progress. delimitation of the content of other events, supplementary events, previous knowledge and expectations of the students) and the experiences associated with the implementation are reported. As presumably every course, this represents work in progress.

Interdisciplinary {\ "a} t as a challenge for ü r e-learning research - Keil, Reinhard; Wessner, Martin (i -com magazine f {\ "u} r interactive and cooperative media)

Between innovation and suitability for everyday use - "Lernstatt Paderborn" - Keil, Reinhard (Paderborn University {\ "a} ts-Zeitschrift)

A coactive support approach for {\ "u} r processes of social reality construction in product creation processes - Holzwei {\ ss} ig, Kai

FPGA-based design and implementation of an approximate polynomial matrix EVD algorithm - Kasap, Server; Redif, Soydan (Proc. Int. Conf. on Field Programmable Technology (ICFPT))

Semi-automatic establishment and maintenance of valid traceability in automotive development processes - Fockel, Markus; Holtmann, Jörg; Meyer, Jan (2012 Second International Workshop on Software Engineering for Embedded Systems (SEES))
The functionality realized by software in modern cars is increasing and as a result the development artifacts of automotive systems are getting more complex. The existence of traceability along these artifacts is essential, since it allows to monitor the product development from the initial requirements to the final code. However, traceability is established and maintained mostly manually, which is time-consuming and error-prone. A further crucial problem is the assurance of the validity of the trace links, that is, the linked elements are indeed related to each other. In this paper we present a semiautomatic approach to create, check, and update trace links between artifacts along an automotive development process.

FPGA implementation of a second-order convolutive blind signal separation algorithm - Kasap, Server; Redif, Soydan (Int. Architecture and Engineering Symp. (ARCHENG))

Comparison of Bayesian Move Prediction Systems for Computer Go - Wistuba, Martin; Schaefers, Lars; Platzner, Marco (Proc. IEEE Conf. on Computational Intelligence and Games (CIG))

A Data Driven Science Gateway for Computational Workflows - Grunzke, Richard; Birkenheuer, Georg; Blunk, Dirk; Breuers, Sebastian; Brinkmann, André; Gesing, Sandra; Herres-Pawlis, Sonja; Kohlbacher, Oliver; Krüger, Jens; Kruse, Martin; Müller-Pfefferkorn, Ralph; Schäfer, Patrick; et al. (Proc. UNICORE Summit)

On the Admission of Dependent Flows in Powerful Sensor Networks - Cohen, Reuven; Nudelman, Ilia; Polevoy, Gleb (Infocom'2012, Orlando, Florida)

Editorial for Algorithmic Aspects of Wireless Sensor Networks - Dolev, Shlomi; Scheideler, Christian (Theor. Comput. Sci.)